B-learning para la enseñanza-aprendizaje de la multiplicación y división en cuarto grado de la Unidad Educativa Particular Eugenio Espejo - Medina Muñoz, María Augusta (2022)
B-learning model resorts to face to face and virtual study. It performs as an important support in the education field; given that, it focuses on hybridization to teach through innovative learning strategies in different areas. The general objective is to determine the incidence of the use of the B-learning model in the teaching-learning process for multiplications and divisions; that is why, these mathematical operations were taken into account in the mathematics area. In the same way, three specific objectives were established which are the following: describe theoretically the B-learning in the teaching-learning process for mathematics; identify the use of the B-learning; and propose a methodological strategy for the application of the B-learning model in the teaching-learning process of multiplication and division to fourth grade students at Eugenio Espejo high school. This study has a mixed approach using scientific, descriptive, inductive, deductive, and synthetic analytical methods; likewise, using the survey technique applied to the forty-one students and interviewing two teachers. The results of the present research study allowed to determine that students know the method; however, they use it infrequently for that they present problems in multiplications and divisions. For this reason, they want to use youtube, wikis, and meet to learn mathematical operations. To conclude, the B-learning method is a mixed process where diverse educational strategies are used during the face-to-face and non-face-to-face learning which is rarely used by fourth grade students for the development of mathematical exercises, so they present problems for their resolution. Therefore, a methodological strategy is proposed for the application of B-learning method which is to stablish an active participation with the teacher being the one who must pedagogically design learning situations to support and interact with the student's knowledge in the subject of mathematics, promoting and motivating students to be collaborative and reflective so that they can function in this new technological world. Keywords: Hybrid learning – teaching learning – mathematics – educational strategies